2016
DOI: 10.1002/psp4.12139
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Characterization of the Pharmacokinetics of Pembrolizumab: A Humanized Anti-PD-1 Monoclonal Antibody in Advanced Solid Tumors

Abstract: Pembrolizumab, a potent antibody against programmed death 1 (PD‐1) receptor, has shown robust antitumor activity and manageable safety in patients with advanced solid tumors. Its pharmacokinetic (PK) properties were analyzed with population PK modeling using pooled data from the KEYNOTE‐001, −002, and −006 studies of patients with advanced melanoma, non‐small cell lung cancer (NSCLC), and other solid tumor types. Pembrolizumab clearance was low and the volume of distribution small, as is typical for therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 18 publications
10
141
1
Order By: Relevance
“…These studies helped to establish that the approved pembrolizumab dose of 2 mg/kg every 3 weeks without dose adjustment in a variety of patient subpopulations is probably the best regimen available at present. (Ahamadi et al 2017). The authors found no clinical significance for variations in sex, baseline performance status, renal and hepatic function, 24:12 tumor type and burden or prior ipilimumab treatment on pembrolizumab exposure (Ahamadi et al 2017).…”
Section: :12mentioning
confidence: 93%
See 1 more Smart Citation
“…These studies helped to establish that the approved pembrolizumab dose of 2 mg/kg every 3 weeks without dose adjustment in a variety of patient subpopulations is probably the best regimen available at present. (Ahamadi et al 2017). The authors found no clinical significance for variations in sex, baseline performance status, renal and hepatic function, 24:12 tumor type and burden or prior ipilimumab treatment on pembrolizumab exposure (Ahamadi et al 2017).…”
Section: :12mentioning
confidence: 93%
“…(Ahamadi et al 2017). The authors found no clinical significance for variations in sex, baseline performance status, renal and hepatic function, 24:12 tumor type and burden or prior ipilimumab treatment on pembrolizumab exposure (Ahamadi et al 2017).…”
Section: :12mentioning
confidence: 93%
“…Statistically significant covariates identified through population PK analysis for approved immune checkpoint inhibitors are shown in Table 2. 66,76,77 Covariates identified as statistically significant varied between the approved agents, but in at least half of cases for clearance included sex, Eastern Cooperative Oncology Group (ECOG) performance status, body weight, tumor type, tumor burden, baseline LDH, estimated glomerular filtration rate, albumin, and immunogenicity and for central volume of distribution included sex and body weight.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The duration of neurologic irAEs is unclear and may be varied. ICPI half‐life varies from 4 to 27.3 days . In 1 study, nivolumab demonstrated 70% occupancy of PD‐1 receptors at ≥2 months with a high affinity and unclear reversibility .…”
Section: Icpi‐associated Aes/toxicitiesmentioning
confidence: 99%
“…Although not specifically studied in the ICPIs, traditional pheresis techniques are sufficient to remove monoclonal antibody therapies such as rituximab . The half‐lives of the ICPI therapies vary widely from 4 to 27 days as do the onset of neuromuscular irAEs . With receptor occupancy as high as 70% for drugs like nivolumab, the role of PLEX specifically to remove ICPIs and the resulting effect on cancer outcomes remains unclear …”
Section: Treatmentmentioning
confidence: 99%